Návrh Assessment centra jako účinného nástroje výběru personálu ve firmě MOSER, a.s. - Válková, Pavla (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Cílem diplomové práce je návrh výběrové metody assessment centre relevantní pro pozice průvodce, odborný prodavač, a pracovník infocentra obsazované ve společnosti MOSER, a.s. Pozornost je zaměřena na vymezení pojmů, zjištění konkrétních pozic pro návrh. Hlavní zájem však je věnován uskutečnění assessment centre a zejména návrhům souvisejícím s jeho uskutečněním.

This master’s thesis is focused on the concept of the assessment centre method relevant for the positions of the guide, the expert salesman and the information centre employee, which are staffed in MOSER, a.s. company. The attention is located on the determination of the terms, the estimation of the specific positions through the project. The main aim was given on the realization of the assessment centre and especially to the proposals related to its implementation.
Concept of AC as an Effective Tool of Personal Assessment in the MOSER Company
Keywords: Assessment centre; přijímání zaměstnanců; výběrové řízení; vhodnost uchazeče; testování uchazeče; Assessment centre; personell recruitment; selection procedure; suitability of expectant; testing of expectant